Effects of different freezing and thawing methods on the quality of giant red shrimp (Aristaeomorpha foliacea) - HAN, Aysegul Tugce; GOKOGLU, Nalan (Acta Aquatica: Aquatic Sciences Journal, 2022)
The aim of this study was to investigate the effects of different freezing and thawing methods on physical, chemical, and sensory characteristics of red shrimp (Aristaeomorpha foliacea). Shell-on and shell-off shrimps were subjected to three different freezing (blast freezing, still freezing and cryogenic freezing) and thawing (on air, in refrigerator and in microwave oven) methods and stored for 30 days at -18ºC. Quality control analyses were carried out in samples after thawing. The lowest total volatile nitrogen and trimethylamine contents, pH values and cooking losses were found in cryogenically frozen shrimp, compared with other freezing methods.  However, cryogenic freezing caused colour fading and softening in texture. It was determined that microwave thawing conditions used in this study are not suitable for thawing of frozen shrimp as it negatively affects texture and colour and increases cooking loss. It was found that blast freezing, and thawing methods preserved the physical, chemical and sensory properties of shrimp better than other methods.Keywords: Aristaeomorpha foliacea; Freezing; Red shrimp; Shrimp quality